High-carbohydrate versus high-fat diets: effect on body composition in trained cyclists - Brown, R. C.; Cox, C. M.; Goulding, A. (Medicine & Science in Sports & Exercise, 2000)
Purpose: Recent research suggesting the benefits of high-fat diets for endurance athletes have been viewed with caution because of the potential negative health consequences, including increased adiposity. Methods: We have examined the effects of a high-fat (HF, 50% of total energy from fat and 37% from carbohydrate) versus a high-carbohydrate (HC, 15% of total energy from fat and 69% from carbohydrate) diet on body fat, lean body mass, and bone mineral density (BMD) in 32 endurance-trained cyclists over a period of 3 months. Body composition was assessed by dual x-ray absorptiometry at baseline and after 3 months. Results: Total and percent body fat, lean tissue mass, and body weight were not significantly different within and between each diet group from baseline to week 12. Total body BMD increased significantly within HF (P = 0.02), but nonsignificantly in HC, over the 12-wk period. Conclusions: In conclusion, during periods of endurance training when energy requirements are high, increasing the percentage of fat in the diet to approximately 50% of total energy does not increase body weight or adiposity because athletes are able to maintain energy balance.